Low lying larynx - Govindaraju, R.; Rajagopalan, R.; Omar, R.; Mukari, S.A.M. (Blackwell Publishing, 2010)
We report a rare case of laryngotracheal anomaly and its possible etiology and mode of presentation. A teenager presented with voice change and a neck lump. Investigations revealed a laryngeal anomaly in which the larynx was hyperdescended. It was accompanied by low lying thyroid gland and hyoid bone together with an absence of a cervical segment of the esophagus and trachea. The anomaly only became noticeable secondary to pubertal changes in the thyroid cartilage of the teenager. An embryological defect during the formation of the laryngotracheal tube and esophagus is a possible explanation of this anomaly. The present case probably represents the third reported of its kind.